Western Sport and Spiritualism - Kosiewicz Jerzy (Sciendo, 2014)
Sport activity of achievement-oriented (professional, Olympic, spectacular character) is first of all exposition of rivalry and striving for variously understood sports success (resulting from measurable or discretionary criteria). It refers to winning a competition or taking another expected place as well as to other forms of satisfaction, such as financial gratification or social (political, ethnic, professional) recognition. Spirituality is here neither an aim, nor an expected value - it constitutes rather an additional or redundant quality. A competitor focuses his/her attention first of all on the main aim assumed in planned or current rivalry. Emotional sensations which are experienced by athletes before, during or after competitions testify to mental and emotional stress which accompanies sports combat.